Dielectric properties of polyamide-imide - Diaham, S; Locatelli, M-L (Journal of physics. D, Applied physics, 2013)
The dielectric properties of poly(amide imide) (PAI) films are investigated in a large temperature range. A moisture-dependent relaxation (γ-relaxation between −100 °C and 20 °C) and a non-cooperative local dipole relaxation (β-relaxation between 40 °C and 200 °C) display an Arrhenius-type behaviour with an activation energy of 0.50 eV and 1.22 eV, respectively. In the near glass transition (Tg) region at 277 °C, a relaxation process (α-relaxation) occurs due to cooperative segmental motions of the chains and follows a non-linear Vogel-Fulcher-Tamman (VFT) temperature dependence with a strong fragility. Simultaneously in the same temperature range, both a conduction process (σ-conduction) and an electrode polarization phenomenon (ρ-relaxation) are also present. The σ-conduction also follows a VFT behaviour but it possesses a lower fragility in the above-Tg region. This discrepancy is assigned to a partial decoupling between ionic transport and segmental chain motions. The dielectric strength of PAI films exhibits a negative temperature dependence. The near-Tg region corresponds to a change from a thermal breakdown mechanism to an electromechanical breakdown due to the glass-liquid phase transition. Above Tg, the formation of a space-charge probably also involves an electro-thermal breakdown mechanism.